Spectrophotometric Characterization of Doped Pr(III) Ion in Saturated Alcoholic Solution of Some Thiosemicarbazone Derived from Carbonyl Compounds - POPLI, ANJU; BHOJAK, NARENDRA; TATER, P.C.; SONI, K.P. (Asian Journal of Chemistry, 2010)
The stereo-environment of doped Pr(llI) ion in saturated solution of some thiosemicarbazones of carbonyl compounds in alcoholic media has been discussed on the basis of various electronic spectral parameters. The various electronic parameters, viz., Judd-Ofelt intensity parameter(Tλ), Slater-Condon (Fk), Landes (ζ4f), intensity of hypersensitive band (3P2) for Racah's (Ek) as well as bonding parameters b1/2 for Pr(III) ion doped in alcoholic saturated solution of thiosemicarbazones derived from thiosemicarbazide and acetophenone, o-bydroxy acetophenone, m-bydroxy acetophenone, o-amino acetophenone, m-amino acetophenone and benzaldebyde.